Application of the PBL Model with Multimedia in Improving Class IV Social and Science Learning Result at SDN Nglanduk 2 - Salma Pigi Taqiyyah, Anisah; Ambarwati , Rosita; Istikomah , Nur (IJCER (International Journal of Chemistry Education Research), 2024)
Teachers still face various challenges in implementing learning in the classroom. Some of them are students who are less active, lack of use of technology, lack of use of concrete objects, and students' social and science learning outcomes that have not yet reached the criteria for achieving learning objectives. The research entitled "Application of the PBL Model with Multimedia in Improving Class IV Social and Science Learning Result at SDN Nglanduk 2" aims to describe the steps for implementing the PBL model with multimedia in improving Class IV Social and Science learning result and identify whether the PBL model with multimedia can improve learning result class IV. The Problem Based Learning (PBL) model is a learning model whose application uses concrete problems to develop problem solving and critical thinking skills so that it can improve student learning outcomes. Multimedia can attract students' attention and make learning more enjoyable. This research was carried out at SDN Nglanduk 2. The classroom action research procedure used refers to the Action Research methodology, namely 1) Planning, 2) Action (Implementation of Action), 3) Observation (Observation), 4) Reflection (Reflection), which is carried out in 2 cycles. Learning evaluation is carried out after the material is presented to find out to what extent students can understand the material being taught. The evaluation results show that there is an increase in learning outcomes, namely in cycle I it was 40%, up 20% to 60% and cycle II, namely 60%, up 40% to 100%. From this Classroom Action research it can be concluded that the application of the Problem Based Learning (PBL) model with multimedia can improve social and science learning for class IV at SDN Nglanduk 2.